1988
DOI: 10.1148/radiology.166.1.2447604
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Doppler US tumor signals with neovascular morphologic features.

Abstract: Abnormal Doppler ultrasound signals were detected in 44 of 47 patients with primary malignant tumors of the liver, kidney, adrenal gland, or pancreas (94%). Two different signal types were noted: a high-velocity signal (n = 38) with Doppler shifts exceeding 3 kHz (at an insonating frequency of 3 MHz) and a very low-impedance signal (n = 9) demonstrating little systolic-diastolic variation. In three patients, both types were present. In 19 patients, histologic (n = 12) and/or angiographic (n = 16) correlation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
0
6

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(134 citation statements)
references
References 0 publications
3
123
0
6
Order By: Relevance
“…37 New interest has developed in contrast-enhanced ultrasound techniques as the unenhanced Doppler ultrasound applied within tumors only depict large vessels (4100 mm) confined to superficial parts of the body. 9,10 Even if previous studies have reported that unenhanced power-mode Doppler ultrasound system is capable of detecting the velocity of blood flow through tumor vessels as small as 10-20 mm in diameter, this imaging system used high frequencies Dynamic assessment of angiogenesis and necrosis in tumor mass C Magnon et al (50 MHz) and a focused transducer to improve the ultrasound signal resolution and focal characteristics. Nevertheless, this technique is not applicable in clinical settings because high frequency (20-100 MHz) decreases exploration depth, impeding the assessment of deep tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 New interest has developed in contrast-enhanced ultrasound techniques as the unenhanced Doppler ultrasound applied within tumors only depict large vessels (4100 mm) confined to superficial parts of the body. 9,10 Even if previous studies have reported that unenhanced power-mode Doppler ultrasound system is capable of detecting the velocity of blood flow through tumor vessels as small as 10-20 mm in diameter, this imaging system used high frequencies Dynamic assessment of angiogenesis and necrosis in tumor mass C Magnon et al (50 MHz) and a focused transducer to improve the ultrasound signal resolution and focal characteristics. Nevertheless, this technique is not applicable in clinical settings because high frequency (20-100 MHz) decreases exploration depth, impeding the assessment of deep tumors.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The detection threshold of CDUS is approximately 100 mm in vessel diameter. 9,10 However, a new clinical approach consists in using microbubble contrast agents, such as Levovist, to increase acoustic signal sensitivity reflecting microvascular perfusion. [11][12][13] In order to predict antiangiogenic effects over a treatment period, contrast-enhanced HFCDUS was used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Very high Doppler shifts have been detected at the peripheiy of numerous malignant tumors, especially in the abdomen [10,11]. It is not likely thata malignant tumorwouldmimicthe high density ofvessels throughout its mass that is seen in hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Often the larger components of the microcirculation lack smooth muscle. They are described as large capillaries, sinusoids or, alternatively, as primitive vascular channels lacking smooth muscle and often consisting of an endothelial layer and connective tissue alone 14 . They show variation in caliber.…”
Section: Discussionmentioning
confidence: 99%
“…They show variation in caliber. Some vessels terminate in wide sinusoids (instead of minute capillaries) or form arteriovenous shunts 14,15 .…”
Section: Discussionmentioning
confidence: 99%